Gender under-representation in teaching: A casualty of the feminisation of teaching? - Davids, N.; Waghid, Y. (South African Journal of Higher Education, 2020)
Much has been written on the relationship between gender and schooling, and teaching. In particular, the focus has been on the significant dis-proportion between female and male teachers, which remarkably, inverts in relation to educational leadership positions. Arguments abound as to the social factors and hegemonies, which have created not only what is referred to as the “feminisation of teaching”, but the risks associated with feminised classrooms and pedagogies, particularly, in relation to boys. Not surprisingly, therefore, an equally dominant narrative calling for the (re)masculinisation of teaching has gained increasing momentum. The basis for this argument is not limited to a seeming need for male teachers as role-models. More disturbing, is the idea that the standing of the profession – invariably measured in terms of salary – might improve if more males are encouraged to become teachers. Our interest in this article is in the patriarchal hegemonies, which give shape to constructions of teaching as “women’s work” in the first place. We argue, that rather than contributing to what has been an overdue preoccupation gender-based socialisations, the concern should be on ensuring that teaching transcends framings of “feminisation” and “masculinisation” so that it serves all teachers and all learners.